Sustainability, family farming and public policies in Brazil: a literature review (Research, Society and Development, 2021)
The present study aims to analyze the literature related to sustainability in family farming and its application in Brazilian public policies. To this end, an analysis of articles related to the theme was conducted, highlighting the main topics, in addition to secondary data from the Federal Government. Through the information collected, it was observed the existence of public policies aimed at food (school and population) and marketing, highlighting institutional channels for the distribution of food produced by these. Sustainability in these production systems also denotes a differentiating characteristic, considering the positive impacts on the environment, the reuse of waste aimed at soil fertility and the possibilities of generating income for farming families.